Makanan Bergizi Untuk Senyum Ceria: Edukasi Gizi Dan Kesehatan Gigi Pada Remaja Di Desa Bilalang Kabupaten Gowa - Magfirah, Febi; Annisa, Nurul; Wijaya, Ayu; Rapiuddin, Risman Abdi; Zulkarnain, Zulkarnain; Nurhaedah, Nurhaedah; Rapang, Yufensius (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Introduction: Dental and oral health is an important aspect in supporting the quality of life of adolescents, but is often neglected due to a lack of knowledge and awareness of healthy eating patterns. Objective: To increase adolescent knowledge about the importance of consuming nutritious food in maintaining dental health. The activity was carried out in Bilalang Village, Gowa Regency, and was attended by 24 adolescents consisting of 14 female adolescents and 10 male adolescents. Method: The methods used included counseling, interactive discussions, and question and answer sessions regarding the types of food that are good for dental health and how to prepare them. Results: There was an increase in participant understanding after the education was provided. Before the activity, most adolescents did not know the relationship between diet and dental health. After the counseling, participants were able to name examples of healthy foods and how to prepare them properly. This activity proves that nutrition and dental health education has an important role in shaping healthy behaviors in adolescents. Conclusion: The series of community service activities with the theme